Analisis Kinerja Keuangan Perusahaan Sebelum Pandemi dan Saat Pandemi Covid-19 - Ahmad Waluya Jati; Wardatul Jannah (Jurnal Akademi Akuntansi, 2022)
This study aims to test whether there are differences in liquidity, leverage, profitability and market ratios from the impact before and during the covid-19 pandemic. The sample in this study consisted of 150 observations from 75 manufacturing sector companies listed on the Indonesia Stock Exchange in 2019 and 2020. The manufacturing sector was used as the object of research because manufacturing sector companies are engaged in the real sector where there are various types of businesses in the sector compared to other sectors. Testing in this study used the paired sample t-test method. The results showed that there were differences in the average values ​​of the liquidity and leverage variables before and during the covid-19 pandemic. While the profitability and PER variables have no difference in the average values ​​before and during the covid-19 pandemic. The results show that during the COVID-19 pandemic, manufacturing companies experienced a decline in the quality of company asset management, so that it had an impact on the company's condition in fulfilling company obligations, although manufacturing companies were still able to make profits even though they experienced a decline.